“di varii instrumenti per misurare con la vista” [“on Various Instruments to Measure with Sight”]. Notes on the Architectural and Urban Survey in the Renaissance (diségno, 2020)
Since ancient times, the main cultures have used methods of measurement, even refined ones, for the study of the territory and for the marking and construction of important works. However, between the 15th and 16th centuries the codification and diffusion of instruments and methods expressly designed for the survey of cities and territory rise. It is a period of cultural and scientific development, as well as of transformation of the methods of knowledge transmission, also thanks to the birth and diffusion of large printing houses. In general, treatises combine rational knowledge with operational and functional applications, putting together theoretical, technical and practical interests. It is precisely thanks to treatises that knowledge spreads outside narrow circles, among a wider educated public (read more).